(3GdbHV GdEdgis - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GYde Cf GdCaYGd hGdGfaYGdGJ JJaGhJ HMjK JaGhJ GdCehQ GdYbdjI GdfaSGfjI hGdLSeGfjI s
(3BNQgG (B:s
(3Yde efgG HbhGfjfgG GdcdjI hGdeSGFd GdLRFjI hdcf GdZOQ ai GeSGc Yf JaGUjdgG hGVM hYfO gPG fNJe GdQSGdI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdadSaI hGdefWbs